2009
DOI: 10.2147/opth.s5555
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, prevalence, and treatment of dry eye disease

Abstract: Purpose:This review article examines the prevalence, etiology, and current therapies of dry eye disease, with special focus on postmenopausal women.Method:A systematic literature search utilizing MEDLINE was conducted to identify peer-reviewed articles related to dry eye published prior to September 2008. The terms “dry eye” and “women” were searched in combination with one or more of the following words or phrases: prevalence, postmenopausal, etiology, risk factors, therapy, medications, surgery, tear film, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
388
2
29

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(426 citation statements)
references
References 36 publications
(44 reference statements)
7
388
2
29
Order By: Relevance
“…13,14 However, a recent systematic review of different ocular lubricants found that eye drops such as hypromellose had the least net changes in improvement compared with carbomer gels and hyaluronic acid products, and low viscosities may explain this. 14 Sodium hyaluronate 0.4% and carboxymethylcellulose sodium 0.5%/glycerin 0.9%, had the highest absolute kinematic viscosities, but also showed steep declines in viscosity with increasing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, a recent systematic review of different ocular lubricants found that eye drops such as hypromellose had the least net changes in improvement compared with carbomer gels and hyaluronic acid products, and low viscosities may explain this. 14 Sodium hyaluronate 0.4% and carboxymethylcellulose sodium 0.5%/glycerin 0.9%, had the highest absolute kinematic viscosities, but also showed steep declines in viscosity with increasing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…However, when there is an environmental stress such as contact lens wear, there could be an increase in the expression of these mediators which then results to tear film dysfunction. 99,100 Ocular allergy is usually considered by ophthalmic practitioners as Type I hypersensitivity. The mechanism of ocular allergy is mediated by immunoglobulin IgE.…”
Section: Allergy and Sensitivitymentioning
confidence: 99%
“…"Cool and dry" conditions are ideal, with recommended RH of about 40%. Likewise, outdoor exposure to sun, dust, and wind has (Gayton 2009). These environmental exposures and trauma may also lead to corneal abnormalities, such as pterygium, which can disrupt the tear film and lead to symptoms of dry eye.…”
Section: Evaporative Dry Eyementioning
confidence: 99%